On the Medical Activities of Anton Pavlovich Chekhov. On the 165th Anniversary of His Birth - L. M. Farkhutdinova (Архивъ внутренней медицины, 2025)
Anton Pavlovich Chekhov gained worldwide fame as a writer, but he was also a doctor by education and dedicated a signifi cant part of his life to medicine. At the university, his studied under outstanding scientists — therapist Grigory Antonovich Zakharyin, surgeon Nikolai Vasilyevich Sklifosovsky, hygienist Fyodor Fyodorovich Erisman. Chekhov began his medical practice as a second-year student at the Chikinskaya Zemstvo Hospital in the Moscow Region town of Voskresensk, where he secured a position as a district physician after graduating from the university. Later, he practiced privately in Moscow. According to colleagues, Anton Pavlovich Chekhov was an excellent diagnostician and a talented psychotherapist. He was distinguished by exceptional kindness, patience and tact in relation to patients. In 1890, he went to Sakhalin, where he was the fi rst to conduct a population census, studied the living conditions of exiles, collected data on diseases and causes of death. Based on the results of his research, he wrote a fundamental work, Sakhalin Island. In the 1890s, he acquired an estate in Melikhovo, 70 km from Moscow, where he served as a zemstvo doctor, fought cholera, built four schools, a fi re station, a post offi ce, a bell tower and a road to the railway station, and organized a public library. In his literary works, Chekhov created a vast gallery of realistic portrayals of doctors. Thanks to his medical experience and knowledge, he professionally accurately depicted clinical portraits of patients with such various diseases as tuberculosis, typhus and typhoid fever, depressive disorder, persecution mania, etc. In 1897, Chekhov suffered from severe pulmonary hemorrhage and was diagnosed with tuberculosis. From 1899, following medical advice, Anton Pavlovich moved to Yalta, where he continued to help everyone who turned to him for medical help. He initiated the construction of a tuberculosis sanatorium and personally contributed a large sum, made numerous charitable donations to the sick. In 1904, Anton Pavlovich’s condition worsened signifi cantly, he was recommended treatment in Germany, at the Badenweiler resort, where Chekhov died on July 2, 1904.